Pemberdayaan Kesehatan Perempuan: Pemeriksaan IVA dan Daun Sirih untuk Keputihan - Fara, Yetty Dwi; Damijah, Damijah; Rosmianah, Rosmianah; Giyarmi, Resti Dian; Lusiana, Ria; Jasmilla, Nia; Delena, Vina Maryu (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2024)
The number of cervical cancer sufferers in Indonesia continues to increase, so early detection is needed to prevent and treat cervical cancer through the IVA method. The aim of this community service activity is to empower women's health in preventing cervical cancer, especially through the implementation of IVA examinations and the use of betel leaves for vaginal discharge. The target of service activities is Women of Childbearing Age (WUS), with partners at the Karta Raharja Inpatient Health Center, West Tulang Bawang Regency. Activities are carried out through the preparation stage, implementation stage and evaluation stage. The preparation stage is carried out by conducting observations and interviews with partners. In the implementation stage, this is done through counseling about cervical cancer, education on maintaining reproductive health through betel leaves, and IVA examinations. The results of the activity showed that there was an increase in participants' knowledge regarding understanding cervical cancer and reproductive health through the use of betel leaves for vaginal discharge. Apart from checking for cervical cancer, it was also discovered that no significant cases were found.